Classroom Transformation for Better Education : Part 1 - A Systematic Review - Nazli, Che Din; Abdul Wafi, Razali; Musli Nizam, Yahya; Raha, Sulaiman; Asrul Sani, Abdul Razak (2023)
In order to accommodate the teaching and learning process, various communication quality between educators and students in a classroom is necessary. Numerous studies have found that classroom acoustic comfort has an impact on both student performance and educator well-being. Several factors influence a classroom's acoustic performance, including material selection, volume, noise disturbance, occupancy, and others. The purpose of this study is to critically review the significant design factors that influence a classroom's acoustic performance, including an in-depth discussion of how the factors manipulate the classroom's acoustic parameters. As a result, the reviewed findings will be presented to demonstrate the relationship between classroom factors and acoustic parameters, and a conceptual framework for classroom acoustic comfort will be proposed as a guideline for designers to use in the future.